Effect of sulfate on low-temperature anaerobic digestion - Madden, Pádhraig; Al-Raei, Abdul M.; Enright, Anne M.; Chinalia, Fabio A.; de Beer, Dirk; O'Flaherty, Vincent; Collins, Gavin (Frontiers in Microbiology, 2014)
The effect of sulphate addition on the stability of, and microbial community behaviour in, low-temperature anaerobic expanded granular sludge bed-based bioreactors was investigated at 15°C. Efficient bioreactor performance was observed, with chemical oxygen demand removal efficiencies of >90%, and a mean SO42- removal rate of 98.3%. In situ methanogensis appeared unaffected at a COD:SO42- influent ratio of 8:1, and subsequently of 3:1, and was impacted marginally only when the COD: SO42- ratio was 1:2. . Specific methanogenic activity assays indicated a complex set of interactions between sulphate-reducing bacteria (SRB), methanogens and homoacetogenic bacteria. SO42- addition resulted in predominantly acetoclastic, rather than hydrogenotrophic, methanogenesis until >600 days of SO42--influenced bioreactor operation. Temporal microbial community development was monitored by denaturation gradient gel electrophoresis (DGGE) of 16S rRNA genes. Fluorescence in situ hybridisations (FISH), qPCR and microsensor analysis were combined to investigate the distribution of microbial groups, and particularly SRB and methanogens, along the structure of granular biofilms. qPCR data indicated that sulphidogenic genes were present in methanogenic and sulfidogenic biofilms, indicating the potential for sulphate reduction even in bioreactors not exposed to SO42-. Although the architecture of methanogenic and sulphidogenic granules was similar, indicating the presence of SRB even in methanogenic systems, FISH with rRNA targets found that the SRB were more abundant in the sulphidogenic biofilms. Methanosaeta species were the predominant, keystone members of the archaeal community, with the complete absence of the Methanosarcina species in the experimental bioreactor by trial conclusion. Microsensor data suggested the ordered distribution of sulphate reduction and sulphide accumulation, even in methanogenic granules.